Effects of heart valve prostheses on phase contrast flow measurements in Cardiovascular Magnetic Resonance – a phantom study. Issue 1 (December 2017) - Richau, Johanna; Dieringer, Matthias; Traber, Julius; von Knobelsdorff-Brenkenhoff, Florian; Greiser, Andreas; Schwenke, Carsten; Schulz-Menger, Jeanette
Abstract Background Cardiovascular Magnetic Resonance is often used to evaluate patients after heart valve replacement. This study systematically analyses the influence of heart valve prostheses on phase contrast measurements in a phantom trial. Methods Two biological and one mechanical aortic valve prostheses were integrated in a flow phantom. B0 maps and phase contrast measurements were acquired at a 1.5 T MR scanner using conventional gradient-echo sequences in predefined distances to the prostheses. Results were compared to measurements with a synthetic metal-free aortic valve. Results The flow results at the level of the prosthesis differed significantly from the reference flow acquired before the level of the prosthesis. The maximum flow miscalculation was 154 ml/s for one of the biological prostheses and 140 ml/s for the mechanical prosthesis. Measurements with the synthetic aortic valve did not show significant deviations. Flow values measured approximately 20 mm distal to the level of the prosthesis agreed with the reference flow for all tested all prostheses. Conclusions The tested heart valve prostheses lead to a significant deviation of the measured flow rates compared to a reference. A distance of 20 mm was effective in our setting to avoid this influence.